Irreversible metamagnetic behaviors and H-T phase diagram in phase separated La0.5Ca0.5Mn1-xAlxO3-δ. Issue 6 (15th March 2023) - Shang, C.; Xia, Z.C.; Dai, H.Y.; Wang, Y.Q.; Liu, D.W.
Abstract: Magnetization relaxation, ac susceptibility, dc magnetization and magnetoelectrical transport measurements have been carried out on Al 3+ -doped manganites La0.5 Ca0.5 Mn1- x Al x O3- δ ( x = 0.05, 0.07, 0.09, 0.10, 0.15). Experimental results suggest that nonmagnetic Al 3+ substituting Mn suppresses the ferromagnetic phase and induces a charge ordered antiferromagnetic phase. The coexistence and competition of these two kinds of interactions result in a spin-glass like state in x = 0.1 and 0.15 system. Obvious hysteresis was observed in both magnetization and resistivity versus temperature and magnetic field curves, suggesting an inhomogeneous metastable phase transition. Upon applying a magnetic field of H C A-F, the Al 3+ -doped samples undergo an irreversible metamagnetic transition from the charge ordering antiferromagnetic insulating to ferromagnetic metallic phase in the low temperature region. Phase diagram in the H C - T plane has been determined according to the magnetization and magnetoelectric transport measurements. The magnetic disorders and antiferromagnetic matrix produced by Al 3+ dopants and spontaneous oxygen vacancies play an important role in the pinning of the FM phase.